Synthesis and characterization of azobenzene based compounds for their photo-induced effects - Yuvaraj, A. R. (2016)
Photonics, in which photo-induced effect can be controlled by light as stimulus has attracted a lot of attentions due to their variety of applications ranging from photonic industries to electronic computer technologies. Among them, optical storage system is a unique subject in which light illumination can alter the molecular structure drastically. These tuning structural property relations are extremely important to fabricate the optical storage devices. Although various light sensitive azobenzene derivatives are available in literature, no detail investigation has been carried out in terms of their controllable photo-induced effects with respect to structure-property relationship. Organic synthesis is a perfect tool, which can manipulate the molecular structure easily to get the desired compounds of azobenzene derivatives by incorporating several functional groups in the molecular architecture. This study gives an idea about the molecular structure and functional groups in azobenzene compounds to vary the time duration of photo-induced effects. Then, evaluated the photo-induced effects and liquid crystalline properties of the synthesized azobenzene compounds such as amides, aliphatic/aromatic spacers, phenol/anisol, fluorine with esters, isoflavones, halogens and siloxanes. The variation observed in the photo-induced effects of the respective compounds in terms of physical and chemical properties such as hydrogen bonding , electron withdrawing effect, hyper conjugation, flexibility, polarity, molecular symmetry, asymmetric effect, photo-crosslinking and electropositive nature. Particularly, amides, aliphatic/aromatic spacers, phenol/anisol, fluorine substituted esters, halogens and siloxane substituted azobenzene derivatives showed long duration of thermal back relaxation due to the action of hydrogen bonding effect, flexibility, polarity, molecular symmetry, photo-crosslinking and electropositive nature. These compounds with long duration of thermal back relaxation are suitable for optical storage technology. On the other hand, isoflavone based azobenzene compounds showed fast photo-response, due to the presence of asymmetric effect in the molecular system. Hence, these isoflavone based azobenzene derivatives are useful to fabricate molecular switches. However, other light sensitive compounds such as, chalcones, stilbenes and imines exhibited lack of photo-induced effects compare to azobenzene compounds. Tacitly, chalcones, stilbenes and imine did not show interesting photo-induced effects as compared to azobenzene compounds. Thus, azobenzene derivatives with various molecular structures and functional groups are suitable to evaluate the photo-induced effects. Also, azobenzene compounds are suitable for optical storage device fabrication. Nevertheless, amides, aliphatic/aromatic spacers, fluorine substituted esters and halogens substituted azobenzene derivatives were liquid crystals. Particularly, these compounds showed nematic and smectic liquid crystal phases. But, chalcones, stilbenes and imine derivatives did not showed liquid crystallinity. The optical storage device was fabricated using 20a, azobenzene compound substituted by olefinic group. The resolution and sharp edges of the letters and pattern, which are stored in the fabricated optical storage device, are showing the novelty of this work. Thus, azobenzene derivatives can be extensively useful for photo-induced optical storage technology.